Pengaruh Struktur Modal, Ukuran Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan LQ45 - Br Simanjuntak, Sri Murtiani; Makmur; Ratna Dewi (CV. Strata Persada Academia, 2025)
This study investigates the influence of capital structure, company size, and profitability on firm value, with a focus on food and beverage companies listed in the LQ45 index on the Indonesia Stock Exchange for the period 2021–2023. Firm value, measured by Price to Book Value (PBV), serves as a key indicator of investor confidence and managerial performance. Employing a quantitative research approach, this study uses secondary data from financial statements and IDX records. The sample was selected using purposive sampling, resulting in three companies that met the established criteria. Multiple linear regression analysis, along with F-test, t-test, and the coefficient of determination (R²), was applied to test the simultaneous and partial effects of the independent variables on firm value. The results show that capital structure and profitability have a positive and significant effect on firm value, while company size has a negative and significant effect. Simultaneously, all three variables influence firm value significantly. These findings highlight the importance of optimizing financial structure and profitability while managing the complexity associated with company size. Future research is encouraged to incorporate additional variables such as liquidity and business risk, as well as to broaden the scope across different sectors for more generalizable insights.